Deep reefs are climatic refugia for genetic diversity of marine forests. (25th November 2015) - Assis, Jorge; Coelho, Nelson Castilho; Lamy, Thomas; Valero, Myriam; Alberto, Filipe; Serrão, Ester Álvares
Abstract: Aim: Past climate‐driven range shifts shaped intraspecific diversities of species world‐wide. Earlier studies, focused on glacial refugia, might have overlooked genetic erosion at lower latitudes associated with warmer periods. For marine species able to colonize deeper waters, depth shifts might be important for local persistence, preventing some latitudinal shifts, analogous to elevational refugia in terrestrial habitats. In this study, we asked whether past latitudinal or depth range shifts explain extant gene pools in Saccorhiza polyschides, a large habitat structuring brown alga distributed from coastal to offshore deep reefs. Location: North‐east Atlantic and western Mediterranean basin. Methods: Genetic structure and diversity were inferred using seven microsatellite loci, for 27 sites throughout the entire distributional range. Ecological niche modelling (ENM) was performed with and without information about genetic structure (sub‐taxon niche structure) to predict distributions for the Last Glacial Maximum (LGM), the warmer Mid‐Holocene (MH) and the present. Results: Both ENM approaches predicted a wider potential distribution in deeper waters than is presently known, a post‐glacial expansion to northern shores and the extirpation of southern edges during the warmer MH. Genetic data corroborated range dynamics, revealing three major genetic groups with current boundaries in the Bay of Biscay and the Lisbon coastal region, pinpointing ancient refugial origins. Despite extensive southern range contraction, the southernmost warmer regions are still the richest in genetic diversity, indicating long‐term persistence of large populations. ENMs suggested that this could only have been possible due to stable refugia in deeper reefs. Main conclusions: The global distribution of gene pools of temperate marine forests is explained by past range shifts that structured both latitudinal glacial refugia and depth refugia during warmer periods. Deep rear edge populations play a fundamental role during periods of extreme climate, allowing persistence and retaining some of the largest genetic diversity pools of the species' distribution.